Case Report: TNF-Alpha Inhibitors to Rescue Pregnancy in Women With Potential Pregnancy Loss: A Report of Ten Cases - Zhong, Zixing; Wang, Yuhan; Wang, Guiqin; Zhou, Feifei (Frontiers in Immunology, 2022)
Miscarriage poses a significant threat to pregnant women globally. Recurrent miscarriages or potential poor embryonic development indicated by early drops in serum human chorionic gonadotrophin (hCG) are even more catastrophic for pregnant women. However, these patients receive either individualized medical intervention supported by limited evidence or no treatment at all. In this study, we report ten patients who shared at least one episode of an early decline of hCG in the first trimester and were treated with compassionate use of tumor necrosis factor-alpha inhibitor (TNFi). They were then followed up regularly with caution. Their hCG trajectory all resumed a normal pattern within one week and the obstetric outcomes were promising. No adverse fetal, neonatal, or maternal health issues have been observed. This case series supports current safety evidence of TNFi and provides new insight into its use in pregnancy when the embryo is in danger. Further well-designed clinical trials should be carried out to consolidate the evidence.